1999
DOI: 10.1159/000024227
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Group 4 House Dust Mite Allergen from Dermatophagoides pteronyssinus and Its Amylase Homologue from Euroglyphus maynei

Abstract: Background: Of the ten recognised groups of Dermatophagoides pteronyssinus allergens, the group 4 is the only group that has not been characterised at the molecular level. Methods: Primers were designed to PCR amplify Der p 4 (D. pteronyssinus) and Eur m 4 (Euroglyphus maynei) cDNA. These fragments were used to screen the corresponding cDNA libraries and the cDNA clones obtained were subsequently sequenced. The coding regions of Der p 4 and Eur m 4 were cloned into the pET expression vector and recombinant his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…The 19-residue N-terminal sequence however only had weak homology to other amylases because this is a region of sequence variation. cDNA cloning of Der p 4 and Eur m 4 revealed that the allergens were 496-amino-acid residue α-amylases with a calculated MW of 57,000 [151]. The sequence contained all of the conserved regions known to be important for amylase structure, calcium binding, substrate and catalytic activity.…”
Section: Group 4 Allergensmentioning
confidence: 99%
“…The 19-residue N-terminal sequence however only had weak homology to other amylases because this is a region of sequence variation. cDNA cloning of Der p 4 and Eur m 4 revealed that the allergens were 496-amino-acid residue α-amylases with a calculated MW of 57,000 [151]. The sequence contained all of the conserved regions known to be important for amylase structure, calcium binding, substrate and catalytic activity.…”
Section: Group 4 Allergensmentioning
confidence: 99%
“…One allergen of 56 kDa, called Blo t 4, has been described as a minor allergen for humans and possesses α-amylase activity. α-Amylases are potent and highly conserved allergens found in mites, fungi, and cereals (Mills et al 1999). …”
Section: Discussionmentioning
confidence: 99%
“…The house dust mite α-amylase showed positive IgE reactivity with 46% of mite-allergic adults and 25% of mite-allergic children. In 1999, Mills et al [7] cloned the genes encoding for the α-amylase from D. pteronyssinus and E. maynei, respectively. The mature Der p 4 and Eur m 4 proteins share about 90% amino acid sequence homology.…”
Section: Discussionmentioning
confidence: 99%
“…α-Amylases contain several well-defined regions in their amino acid sequences that are highly conserved across a broad spectrum of organisms that are of evolutionary distinct origins. Group 4 allergens from Dermatophagoides pteronyssinus and Euroglyphus maynei have been shown to contain some of these conserved regions [7]. The 10 recognized invariant residues within these conserved regions include 7 thought to be involved in catalysis and substrate binding in the active site and 3 that are structurally important, and they are present in both species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation